2004
DOI: 10.1016/j.pain.2004.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Do medical factors predict disability in older adults with persistent low back pain?

Abstract: Persistent low back pain (LBP) is one of the most common and challenging persistent pain conditions in older adults. Medical comorbidity also is common in these individuals, but its impact on disability has not been examined. The purpose of this study was, using a cross-sectional design, to examine the functional impact of pain-related and general medical comorbidity on 100 community dwelling older adults (mean age 74.3) with persistent mechanical LBP. Subjects received a structured history and physical examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
2
17

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 33 publications
5
31
2
17
Order By: Relevance
“…Use of health care services increases among those suffering from incapacitating chronic 2,3,15,21 and intense pain, 3,12,21,24 as seen in this study.…”
Section: Discussionsupporting
confidence: 65%
“…Use of health care services increases among those suffering from incapacitating chronic 2,3,15,21 and intense pain, 3,12,21,24 as seen in this study.…”
Section: Discussionsupporting
confidence: 65%
“…Algumas características da dor estão associadas a maiores déficit funcionais e incapacidade, como dores intensas 16,26,35,39,40 , múltiplos locais de dor 28,36,39 , dores em região dorsal 8,17,29,30,34 e em membros inferiores 17,34,39 .…”
Section: Conclusãounclassified
“…Older individuals (60 years or older) in the Wittink et al 53 study reported similar pain intensities but better psychological outcomes than their younger counterparts. Weiner et al 50 found an inverse relationship between pain duration and disability in elderly subjects. In addition, older individuals may consider maintenance of safe and independent movement and function to be a higher priority for intervention if the pain they are experiencing is manageable from their point of view.…”
Section: Figurementioning
confidence: 97%
“…Additionally, the literature reporting the factors associated with CLBP as people age is sparse. Weiner et al 50 examined measures of lumbar flexibility and radiographic evidence of degenerative disease in a study of elders with persistent low back pain (mean  SD, 74.3  4.7 years). Impairments consistent with possible joint restriction were noted with both measures; however, neither demonstrated an association with function or disability in the subjects.…”
Section: Figurementioning
confidence: 99%